DETECTION OF RICE WEEVIL LIFE STAGES IN RICE SEEDS USING RADIOGRAPHIC TECHNIQUES - Ivan BRICEÑO-PINZON; Raquel Maria PIRES; Mayra Alejandra RINCÓN; Eliana Donizete ANDRADE; Flávia Barbosa BOTELHO; Julia Lima BAUTE; Geraldo Andrade CA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Radiographic analysis is a nondestructive technique used to analyze the quality of seed lots and has shown efficiency and precision by reducing subjectivity and time in the performance of laboratory tests. The objective of this study was detect the developmental stages of S. oryzae (Coleoptera: Curculionidae) using X-rays. Healthy seeds of the rice cultivar CMG-1590 were infested with S. oryzae adults and evaluated by X-ray analysis according to the times estimated for the development of the stages weevil, namely, 5, 10, 20, 30 and 40 days after infestation. Additionally, analysis of the infested seeds were performed to evaluate the different life stages of the S. oryzae present. Statistical differences were observed regarding the levels of infestation detected between treatments. The egg, larva and adult stages of development were detected, except for the pupal stage, which was not possible to observe. Damaged seeds and empty seeds were also detected as a result of the feeding habit and life cycle of the insect. In conclusion, the X-ray analysis allowed us to verify the infestation of S. oryzae in rice seeds, as well as characterize the development cycle of the weevil and identify its life stages.